Tingkah Laku Owa Jawa (Hylobates moloch) di Fasilitas Penangkaran Pusat Studi Satwa Primata, Institut Pertanian Bogor - Septiantina Dyah Riendriasari; Entang Iskandar; Jansen Manansang; Joko Pamungkas (Jurnal Primatologi Indonesia, 2009)
The Javan Gibbon is a primate species endemic to Java, Indonesia and considered as an endangered species (IUCN 2008). The Primate Research Center of Bogor Agricultural University (PRC-IPB) in cooperation with Taman Safari Indonesia have established an ex situ breeding facility for the Javan Gibbon to support conservation program. The breeding was started in 2003, and up to recently, the pair of Javan Gibbons ( 15 and 7 years old) has had three offspring, and still occupy one common cage. Assessment of the Javan Gibbon’s behavior in captivity especially to the family with five individuals was conducted using focal animal sampling to provide basic behavioral data.  Moving was the greatest frequency (45.70%) of each individual compared to other behaviors, while resting was the greatest duration that occurred to the parents, and playing was the greatest duration (18.02%) to the offspring respectively.    Keywords : behavior, javan gibbon, endangered, captive breeding